A new species of Forcipomyia (Phytohelea) from Argentina (Diptera: Ceratopogonidae) - Marino, Pablo Ignacio (2013)
The adult and pupa of a new species of Forcipomyia (Phytohelea) are described, illustrated and photographed. Pupae were collected from water held by Eryngium L. sp. (Apiaceae) in Corrientes province, Argentina and reared to adults in the laboratory. Adult and pupa are compared with the closely related congener F. (P.) jocosa Saunders, and the pupa is also compared with that of F. (P.) bromelicola (Lutz).